No new problem for the Trinity: A reply to Mooney - Czepielik, Agnieszka (Religious studies, 2026)
The Father is God, the Son is God, the Holy Spirit is God, but there is only one God - this is the traditional problem of the Trinity. Recently, a new problem for the doctrine of the Trinity has been developed. God is triune, the Son is God, but the Son is not triune - that’s the new Triunity Problem. In this article, I show that adopting any solution to a traditional problem makes it possible to solve the new problem without incurring additional costs. I distinguish possible types of solutions to the traditional problem and point out the costs involved. I then show how each of these solutions can be used and developed to solve the new problem.